RECONSTRUCTION OF THE ROLE OF CUSTOMS ADMINISTRATION IN FREE TRADE ACCORDING TO THE LEGAL POLITICS OF INTERNATIONAL COOPERATION - Ardiansyah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
The role of customs is vital in the implementation of FTAs. However, relatively little research is devoted to the role of customs under the FTA scheme. The juridical problem regarding the role of the customs authority from the aspect of international trade law can be seen from the many disputes over FTA import duty tariff by customs. International disputes regarding the Rules of Origin (RoO) continue to escalate more with the increasing volume of international trade devoted to preferential treatment, such as the Free Trade Agreement (FTA) scheme. Identification of the problems studied in this study is how to reconstruct the role of customs in free trade under international cooperation legal politics. Normative legal research is carried out using two approaches, namely: a conceptual approach (conceptual approach) and a statutory approach (statute approach), to examine problems in the content of legal norms, which are the legal basis for Customs Administration actions. The research aims to direct the establishment of law in the field of FTAs in line with Indonesian legal and constitutional politics. The results findings indicate that there is a conflict of interest in the main task of collecting state revenues with the consequences of the FTA in the form of tariff reductions. The target of state revenue from the international trade sector is eroded with the reduction in FTA import duties. A reconstruction of the role of Customs is needed in the development of FTA law in line with The Politics of International Cooperation Law. The reconstruction is carried out, firstly, by reforming the customs vision so that it is not merely revenue-oriented. Secondly, Reconstructing customs law that is clear, detailed, simple, and has legal certainty so that there is no ambiguity, multiple interpretations, and inconsistency in its application. Then, building a new paradigm of compliance framework based on cooperative compliance to create transparency and mutual understanding between importers and customs authorities and, finally, enhance tariff liberalization and synergy with Tax Administration.